Influencia del Taller de Títeres en la disminución de la Indisciplina en los niños de 4 años de edad del C.E.E. “Rafael Narváez Cadenillas” de la ciudad de Trujillo - Ramírez Bahamonde, Lucía Jimena (2018)
In the present research report entitled "Influence of the Puppet Workshop in the decline of indiscipline in children of 4 years of age of C.E.E. "Rafael Narváez Cadenillas" in the city of Trujillo, "was the primary objective of helping to reduce indiscipline in children's research._x000D_ The problematic reality, background and justification were taken into account and then formulate the statement of the problem and the hypothesis, raise the objectives, carry out the operation of the variables and elaborate the theoretical framework._x000D_ The statement of the investigation problem was: To what extent the Títeres Workshop helps to reduce indiscipline in children of 4 years of age of C.E.E. "Rafael Narváez Cadenillas" From the City of Trujillo? And the hypothesis: To reduce the indiscipline presented by the children of 4 years of age of C.E.E "RAFAEL NARVÁEZ CADENILLAS" through the puppet workshop._x000D_ The investigation was applied and performed with a sample of a population, being the design of a quasi experimental research, with an experimental group and a control group with pre and post test. To obtain the results, a research scale was applied as a research instrument._x000D_ The results obtained were used to develop and then apply the corresponding activities aimed at helping children improve their problematic situation.